Information quality, adoption of climate-smart varieties and their economic impact in flood-risk areas - Veettil, Prakashan Chellattan; Raghu, Prabhakaran T.; Ashok, Arathy (Cambridge University Press, 2021)
Weather extremes which are accelerated by changing climate greatly decrease agricultural productivity, resulting in severe economic losses and losses of livelihood of the poorest marginal communities. The adoption of stress-tolerant rice varieties (STRVs) is recommended as a best technology fix for risk adaptation. Although STRVs provide better outcomes with no yield penalty, farmers' decisions to adopt new STRVs are influenced by a multitude of factors, most importantly information exposure. We used a sequential logit model to analyze the impact of information access and information quality on adoption decisions regarding STRVs in flood-risk areas. Over the years, we found that STRVs adoption has become scale neutral, but adopters have significantly higher access to information. The estimates showed that 48 per cent of the farmers having access to information decided to adopt STRVs. When information reaches 50 per cent of the rice farmers in flood-prone areas, the estimated additional annual income is US$235 million.